Genetic evaluation of Gir bulls under associated herd progeny testing programme - SINGH, UMESH; RAJA, T V; ALYETHODI, R R; MURTHY, K S (The Indian Journal of Animal Sciences, 2019)
A study was conducted to predict the expected breeding values of 6 Gir bulls inducted under the All India Coordinated Research Project on Cattle. A total of 222 first lactation 305 days records of Gir daughters born between 2013 and 2017 were analyzed by Best Linear Unbiased Prediction (BLUP) method using Model VIII of LSMLMW software. The BLUP model included the herd-year-season effect as fixed factor and sires as random factor. The overall average expected breeding value (EBV) was 2563.79 kg. The breeding values of Gir sires ranged between –71.13 to +150.71 kg. The results of the study revealed that the BLUP method discriminated the sires for their breeding values to a larger extent so that the genetically superior bulls can be discriminated from the poor bulls. Based on the results, use of frozen semen doses of two Gir bulls, viz. Pankaj and Bhavik is recommended to breed the Gir cows for increasing the milk production in subsequent generations.